2013
DOI: 10.4103/0974-8520.127705
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of diet and life style in the etiopathogenesis of Urdhwaga Amlapitta (non-ulcer dyspepsia)

Abstract: For a long time, infectious (communicable) diseases were the biggest killer diseases globally. But now, the trend is changing toward increased prevalence of chronic diseases with causative factors mostly related to diet and lifestyle. Among them, Urdhwaga Amlapitta (non-ulcer dyspepsia), a gastrointestinal tract (GIT) disorder, has acquired majority of the share with causative factors like improper diet and habits, stress, spicy irritant food, oily foods, bakery products, etc., A survey study was conducted on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…[5][6][7] Publications on preclinical and clinical studies on food ingredients like dairy products, pomegranate, garlic, and other spices 8,9-11 Some clinical work on the effect of a particular diet on a specific condition has also been done. [12][13][14][15][16][17][18][19][20][21][22][23][24] However, the research work was found to be inconclusive with basic lacunae such as lack of standardization and standard operating procedure for preparation and administration of diet without a watch on compliance and specific outcome. The studies also had considerably short duration, conducted on a small and non-representative sample.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7] Publications on preclinical and clinical studies on food ingredients like dairy products, pomegranate, garlic, and other spices 8,9-11 Some clinical work on the effect of a particular diet on a specific condition has also been done. [12][13][14][15][16][17][18][19][20][21][22][23][24] However, the research work was found to be inconclusive with basic lacunae such as lack of standardization and standard operating procedure for preparation and administration of diet without a watch on compliance and specific outcome. The studies also had considerably short duration, conducted on a small and non-representative sample.…”
Section: Resultsmentioning
confidence: 99%
“…Also, food and life style related factors might have led to this result which is supported by the fact that gastrointestinal disorder, is caused mainly by improper diet and habits, stress, spicy irritant food, oily foods, etc. [ 8 ]. Due to the lack of diagnostic facilities in the camp setting, diseases requiring diagnostic techniques were included less in number (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Main causes for the disease are improper diet, not following AharaVidhiVisheshayatana, Viruddhahara, and Asatmyaahara which is the main factor of impaired digestive function, i.e., Mandagni. [2] Risk factor…”
Section: Agnimentioning
confidence: 99%
“…Among them, nonulcer dyspepsia, a gastrointestinal tract disorder, acquires majority of the share. [2] Amlapitta is a burning problem of today's society. This has given rise to many other serious diseases.…”
mentioning
confidence: 99%